2023
DOI: 10.3389/fpubh.2023.1079992
|View full text |Cite
|
Sign up to set email alerts
|

Understanding public support for COVID-19 pandemic mitigation measures over time: Does it wear out?

Abstract: BackgroundCOVID-19 mitigation measures intend to protect public health, but their adverse psychological, social, and economic effects weaken public support. Less favorable trade-offs may especially weaken support for more restrictive measures. Support for mitigation measures may also differ between population subgroups who experience different benefits and costs, and decrease over time, a phenomenon termed “pandemic fatigue.”MethodsWe examined self-reported support for COVID-19 mitigation measures in the Nethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Our results thus contradict previous studies finding that pandemic fatigue led to lower adherence to behavioural guidelines over time (Franzen & Wohner, 2021;Ross & Dutton, 2023), likely because we controlled for changes in pandemic severity (Wilson, 2023). Our study expands on earlier analyses that indicated that support for measures remained high throughout the first year of the pandemic in the Netherlands (De Wit et al, 2023), showing that even with prolonged duration, people increased their adherence to behavioural guidelines when the pandemic situation became more severe.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results thus contradict previous studies finding that pandemic fatigue led to lower adherence to behavioural guidelines over time (Franzen & Wohner, 2021;Ross & Dutton, 2023), likely because we controlled for changes in pandemic severity (Wilson, 2023). Our study expands on earlier analyses that indicated that support for measures remained high throughout the first year of the pandemic in the Netherlands (De Wit et al, 2023), showing that even with prolonged duration, people increased their adherence to behavioural guidelines when the pandemic situation became more severe.…”
Section: Discussioncontrasting
confidence: 99%
“…COVID-19 preventive measures have been introduced to protect public health, but their adverse psychological, social, and economic impact may have weakened their popular support over time. We found that during the first two years of the pandemic, overall support declined for all measures and was systematically lower for those measures that were more socially restrictive [ 16 ]. More specifically, differences in support were most evident among different age groups (i.e., higher support for hygienic measures among younger participants and higher support for measures restricting social contacts among older participants), and less so for other demographical factors such as living situation or educational level.…”
Section: Findings To Datementioning
confidence: 99%
“…Furthermore, during the COVID-19 pandemic, authori ties asked people to reduce clusters of infection by practicing social distancing (Fraser & Aldrich, 2021). While these measures aimed at reducing the congestion of hospital beds and preventing deaths, especially in settings that share higher infection rates (Hamidi et al, 2020;Van Bavel et al, 2020), they were met with antagonism in various settings (De Wit et al, 2023;Guglielmi et al, 2020).…”
Section: What Do These Findings Mean?mentioning
confidence: 99%